Aby Warburg and the image in motion - Michaud, Philippe-Alain (New York : Zone Books, 2007)
Aby Warburg is best known as the originator of the discipline of iconology and as the founder of the institute that bears his name. This text shows that Warburg's own project was remote from any positivist or neo-Kantian ambitions.
This translation from French originally published: 2004
Onderzoek KASK (1KA-OF1001)
boek